Question
upstudy study bank question image url

Wo angies in an equilateral triangie are \( (a+b) \) and \( (2 a-10 b) \) degrees Find the values of \( a \) and \( b \).

Ask by Bird Daniel. in Papua New Guinea
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( a = 55^\circ \) and \( b = 5^\circ \).

Solution

To solve for \( a \) and \( b \) in an equilateral triangle where the angles are given by \( (a + b) \) and \( (2a - 10b) \) degrees, follow these steps: 1. **Understanding an Equilateral Triangle:** - In an **equilateral triangle**, all three angles are equal. - Each angle in an equilateral triangle is **60 degrees**. 2. **Setting Up the Equations:** - Since all angles are equal, we can set: \[ a + b = 60^\circ \] \[ 2a - 10b = 60^\circ \] 3. **Solving the Equations:** - From the first equation: \[ a = 60^\circ - b \] - Substitute \( a \) from the first equation into the second equation: \[ 2(60 - b) - 10b = 60 \] \[ 120 - 2b - 10b = 60 \] \[ 120 - 12b = 60 \] \[ -12b = -60 \] \[ b = 5^\circ \] - Substitute \( b = 5^\circ \) back into the first equation to find \( a \): \[ a = 60^\circ - 5^\circ = 55^\circ \] 4. **Final Solution:** \[ a = 55^\circ \quad \text{and} \quad b = 5^\circ \] **Answer:** After simplifying, a is 55 degrees and b is 5 degrees.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

In an equilateral triangle, all angles are equal and sum up to \( 180 \) degrees. This means if two angles are \( (a+b) \) and \( (2a-10b) \), we can set up the equation: \[ (a + b) + (2a - 10b) + x = 180 \] Where \( x \) is the third angle which is also equal to \( (a + b) \) since all angles in an equilateral triangle are the same. Therefore, we have: \[ (a + b) + (2a - 10b) + (a + b) = 180 \] Combining the terms, we get: \[ 4a - 8b = 180 \] To simplify, divide the entire equation by 4: \[ a - 2b = 45 \] Now we have one equation. Since \( a + b \) should also equal the third angle, we know: \[ a + b = 60 \] Now we have two equations: 1. \( a - 2b = 45 \) 2. \( a + b = 60 \) We can solve these equations. From the second equation, we can express \( a \): \[ a = 60 - b \] Substituting \( a \) into the first equation: \[ (60 - b) - 2b = 45 \] Simplifying this gives: \[ 60 - 3b = 45 \] Now, isolating \( b \): \[ 3b = 15 \\ b = 5 \] Now substitute \( b = 5 \) back into the equation for \( a \): \[ a + 5 = 60 \\ a = 55 \] Thus, the values of \( a \) and \( b \) are: \[ a = 55, \quad b = 5 \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy